Distribution of nontuberculous mycobacteria in patients with and without HIV/AIDS in Chongqing. (15th March 2022) - Nie, Jingmin; Deng, Xizi; Zeng, Qingling; Du, Xiang; Chen, Yaokai; Hu, Fengyu
Abstract: Introduction: In this study, the distribution of nontuberculous mycobacteria (NTM) strains in patients with and without HIV/AIDS in Chongqing, China was evaluated. Methods: A retrospective study was performed in January–December 2020 at Chongqing Public Health Medical Center. NTM strains were assessed by a multi locus phylogenetic analysis. The distribution of NTM strains in HIV/AIDS and non‐HIV/AIDS groups was compared. CD4+ cell counts, imaging changes, and characteristics of mycobacterial species were determined. Results: In total, 324 patients with NTM infection (50 patients with HIV/AIDS and 274 patients without HIV/AIDS) were included. The most common etiological agent was M . abscessus (29%), followed by M . paraintracellulare (12%) and M . colombiense (11%). Predominant NTM species were M . avium (26%), M . colombiense (24%), and M . kansasii (18%) in patients with HIV/AIDS and were M . abscessus (32%), M . paraintracellulare (13%), M . fortuitum (10%), and M . intracellulare (10%) in patients without HIV/AIDS. For a CD4+ cell count of <200/μl, the predominant species were M . avium in the HIV/AIDS group and M . abscessus in the non‐HIV/AIDS group. With respect to radiologic characteristics, different NTM strains were associated with distinct imaging manifestations; for example, M . marseillense, M . kansasii, and M . parasenchytosis were more likely to induce cavities. Imaging cavities, bronchiectasis, and acinar‐like changes were more common in the non‐HIV/AIDS groups. Conclusions: The infection rates of HIV and NTM in Chongqing are high, while M . abscessus, M . paraintracellulare, and M . colombiense are the main pathogens causing NTM diseases in Chongqing, and NTM strains differed significantly between patients with and without HIV/AIDS. Monitoring these indicators can help develop prevention strategies.